Journal of neurology (Steinkopff, 1974)
The Journal of Neurology is an international peer-reviewed journal which provides a source for publishing original communications and reviews on clinical neurology covering the whole field.
Keywords: Neurology; Neurosurgery; neurologie; neurochirurgie